FIRST RECORDS OF THE ALIEN SYCAMORE SEED BUG BELONOCHILUS NUMENIUS IN SERBIA (HETEROPTERA: LYGAEIDAE) (Acta Entomologica Serbica, 2016)
The North American species Belonochilus numenius (Say, 1832) (Hemiptera: Heteroptera: Lygaeidae: Orsillinae) was first recorded in Europe in 2008, and is now present in most of the countries of Southern and Central Europe. The first specimen of B. numenius in Serbia was found in 2011 in Sremska Kamenica; it was later recorded in Zasavica, Mokrin and Novi Sad.